Using the TIDieR checklist to describe the intervention of the Sedation and Weaning in Children (SANDWICH) trial. Issue 3 (22nd June 2022) - Tume, Lyvonne N.; Blackwood, Bronagh; McAuley, Daniel F.; Morris, Kevin; Peters, Mark J.; Jordan, Joanne; Walsh, Timothy Simon; McIlmurray, Lisa
Abstract: Background: Published reports of complex interventions in randomized controlled trials often lack sufficient detail to allow trial replication and adoption into practice. Aim: The aim of this paper is to describe our experience of using the Template for Intervention Description and Replication (TIDieR) checklist in reporting a recent trial of sedation and ventilation weaning in critically ill children (the Sedation and Weaning in Children [SANDWICH] trial). Methods: The TIDieR 12‐point checklist has been used to detail and describe the specific SANDWICH trial intervention and methods of implementation. Results/Discussion: Overall, we found the checklist a useful tool to direct and ensure consistency of reporting of our complex intervention used in a multi‐centre clinical trial. We experienced some minor limitations in classifying training materials and delivery mode into one item because of the overlapping nature of this component. Conclusion: Using the TIDieR checklist to report complex interventions tested in trials provides a structured, systematic way of describing necessary detail. This allows clinicians to understand the theory behind the intervention, how it should be delivered, and the resources required. Relevance to Clinical Practice: The SANDWICH intervention had a significant beneficial effect on reducing time on ventilation for children. The detailed description of the team‐based intervention will aid replication, implementation and monitoring of fidelity in other paediatric intensive care units.